PENGARUH PREFERENSI RISIKO, ETIKA DAN PARTISIPASI PENYUSUNAN ANGGARAN PADA SENJANGAN ANGGARAN PENDAPATAN DI PEMERINTAH PROVINSI BALI - Triadhi, Nyoman Andika (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2014)
Budgeting at the local government budgeting process undergone many debates. Budgetary slack in the budgeting process in Local Government is influenced by factors such as risk, ethics and participation in the preparation of the budget. Inconsistencies research results made ??researchers feel the need to transform and perform further research. This study aims to investigate the influence of risk preferences, ethics and budget participation on revenue budgetary slack in Bali Province. Data was collected through questionnaires given to employees of middle-and lower-level. The results showed that risk preference and ethics have a negative effect on earnings in the preparation of the Bali Province, while the budgetary participation has a positive effect on budgetary revenues in Bali Province.   Keywords: Bali Province, budgetary slack, risk preference, ethics, budgetary participation
Keywords: Bali Province, budgetary slack, risk preference, ethics, budgetary participation